(untitled) (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2024)
This research is based on the majority of people in Tanah Datar Regency who work as farmers, one of which is fish cultivation. Based on this, researchers want to know the welfare of the fish farming community in Tanah Datar Regency. This research aims to determine the welfare of the fish pond cultivator community according to an Islamic economic perspective in Tanah Datar Regency. The research approach used is descriptive qualitative. The primary data source in this research is the fish farming community, obtained from interviews. Meanwhile, secondary data sources are documents and other supporting data. The data validity checking technique used in this writing is the source triangulation technique. The results of this research show that the fish pond cultivation business in Tanah Datar Regency is very beneficial and can improve the welfare of the community as seen from the aspects of maintaining religion, soul, reason, heredity and property, so these five aspects have also been fulfilled and it can be concluded that fish pond cultivators are prosperous. from an economic and Islamic economics perspective.